How to improve communication competence of government leading officials in intercultural environment?—the driving role of intercultural psychological factors - Wang, Ting; Li, Jingping (Frontiers in Psychology, 2025)
IntroductionIn the context of the Belt and Road Initiative, inland China city such as Xi’an, is in a situation where native and foreign cultures are intertwined. Government leading officials are crucial to the effectiveness of intercultural communication in the region, but little attention has been paid to the government leading officials’ intercultural communication competence (ICC) and its factors.MethodsIn this investigation, the factors of ICC were expanded to psychological factors (attitude and awareness of intercultural communication), knowledge factors (native and foreign cultural knowledge), and skill factors (resilience and pragmatic skills for intercultural communication). A structured questionnaire was administered to 578 government leading officials in Xi’an. The collected data were analyzed using descriptive statistics, factor analysis, difference analysis, and regression analysis.ResultsThe study revealed that among the factors of ICC, intercultural communication awareness exerted the strongest influence on resilience skills. Additionally, the highest foreign language score, participation in training, education status, and frequency of contact with foreigners significantly impacted ICC.ConclusionThis study expanded existing intercultural communication models. Based on the results of the analysis, possible measures to promote ICC of government leading officials were proposed, including the enhancement of foreign language skills, participation in professional training, intercultural situational education, and study abroad.